Narrative Review: Analisis Kadar Asam Lemak Bebas dan Kadar Air dalam Minyak Jelantah Sawit - Amelia Handayani Burhan (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2021)
Free fatty acids in used cooking oil are long chain fatty acids that are not esterified. Free fatty acids contain long chain saturated fatty acids. The more consumption of free fatty acids, will increase the level of Low Density Lipoprotein (LDL) in the blood which is bad cholesterol. The water content in cooking oil causes oxidation of the used cooking oil. Oxidation also causes the oil to darken. It is predicted that the colored compounds in the fried ingredients will dissolve in the oil and cause the formation of a dark color. This study aims to describe the techniques for determining the free fatty acid content and water content in used cooking oil. This study uses a narrative review. Literature search uses strategies, such as searching for articles in research journal databases, searching through the internet and reviewing articles. The articles selected by the researchers were based on the desired criteria, namely the quality of used cooking oil in terms of acidity and water content. Search articles using the Google Scholar search engine, research gate and science direct which have been determined according to inclusion and exclusion. Extraction results from 10 journal articles were selected through inclusion and exclusion stages according to research questions with PICO parameters and there was 1 article examining free fatty acid levels using the spectrophotometric method with levels of 0.270% to 0.363%. The free fatty acid content of 9 articles that used the alkalimetric titration method had levels between 0.202% to 12.07%. There are 7 samples of used palm oil that still meet the standards of SNI 7709:2012. The water content of used cooking oil was obtained using the gravimetric method with levels between 0.01% to 5.18% and there were 8 samples that still met the standard of SNI 7709:2012.